Management accounting development and practices in Bangladesh - Sharkar, Mohammad Zakir Hossain; Sobhan, Md. Abdus; Sultana, Shahida (BRAC University, 2010)
The more the development of the market economy, the more the significance of management accounting. To keep pace with this increasing market economy, it becomes imperative for the organizations to adopt new management accounting tools and techniques. It is also important for the Bangladeshi organizations. This paper seeks to obtain an overview of the management accounting practices in the listed manufacturing companies of Bangladesh. Data has been gathered by a questionnaire survey from eight manufacturing sectors. The analysis has revealed that though there is difference in extent of practices among the sectors, all sectors fail to practice some newly developed techniques. If this trend continues, Bangladeshi organizations will lag behind in the race of global competitiveness and comparative advantages. It is therefore, some policy recommendation has been made to improve and fasten the management accounting practices.